Trends in orthodontic scientific contributions: An evaluation based on the American Association of Orthodontists annual sessions - Ignacio García-Espona; Ahmed Amine Kanine-Ait-Zalim; José Antonio Alarcón; Cristina García-Espona; Eugenia García-Espona (PLoS ONE, 2025)
Scientific contributions (lectures and posters) to the American Association of Orthodontists (AAO) annual sessions from 2013 to 2023 were investigated with the aims of analysing the contributions of each country and their efficiency, presentation trends, and gender differences during these years as well as the most frequent topics and their evolution. Official data were requested from and provided by the AAO secretary. The year and type of presentation; the name, country and gender of the first author; and the full title of the presentation were considered. In addition, six national indicators that could determine the quantity and quality of scientific production were obtained from the Our World in Data website with regard to the countries that made the greatest contributions to the AAO annual sessions. The USA featured the largest number of lecturers (69.44%), while the presentations of posters were more balanced among the 4 countries that exhibited the highest levels of production (i.e., Brazil, the USA, Mexico and South Korea). Brazil was the main country to perform above expectations. The COVID-19 pandemic resulted in a significant reduction in the number of poster presentations. The male/female ratio was close to 3:1 in terms of lectures and close to 1:1 in terms of posters. In 2023, women presented more posters than did men. The terms clear/aligners and digital were strongly present, and the terms maxillary, adults, and expansion were used increasingly frequently, while the use of the terms brackets or cephalometry decreased. American lecturers included terms that differentiated them from lecturers in other countries. The nationalities of lecturers are not closely related to those of posters, particularly with regard to the USA, Brazil, Canada, Mexico and Turkey. Research spending and economic level are the most significant factors with respect to the type and number of a country’s contributions. Concerning gender, a clear imbalance in favour of men persists among lecturers. Increased distance from the USA makes it more difficult for women to serve as lecturers. An emergent paradigm shift in current topics towards a focus on the terms clear/aligners and digital in lectures is evident.